(untitled) (Journal of the College of Education for Women, 2019)
Thank God also taught us that thanks . thank meets the blessings and rewards mazidk glory we have no knowledge except what you have taught you Alim hakim , not counted praise you as yourself praised and pray and to recognize the envoy mercy to the worlds , prophet Mohammed and his family and companions and guided to the day of judgment .But after :Aware of the interpretation of the most important science needed by Muslims because God Almighty sent down the Quraan to be a way of the life for Muslims is subject to a healing for what is in the breasts and it slaham and flaham and has spared the nation from crisisThe stats of the monks , like other verses talking about Christians and Jews and what they have invented in the religion of Allah . he also speaks to christians were complaisant yen from Jews and how their acceptance of the Islamic religion according to a simple indication they were less hostile to the Muslims of the Jews as the they talk about who they take money for that asdor people for the sake of Allah . talk about who hoard and spend it not God and preached a grievous punishment .talk about those who associate partners in God and worship gods other than God , and who invented the monastic and Maraoha right sponsorship all of the things that must stand with the people mtazin the lessons and putting in their daily lives , especially in these times when many of them retuned to the actions of the infidels and kabbanhm and both in doctrine or in morality .Research MethodologyFollowed analytical method which is based on scientifically founded by well- known from the introduction and pave the four demands and conclusion .The first requirement : includes continued proof and creativityThe second requirement : the monks eat peoples wealth unlawfullyThe third requirement : monks as lords besides AllahThe fourth requirement : monks who feared GodConclusionI end this scientific tour blessed with the verses of monks and analytical study .thanks God almighty on his generosity , which has no boundaries and pray on the prophet Mohammed his generosity. Lines what I found out from the findings of the facts summarized as follows :1 – the idea of monastic life that invented came out of themselves when God almighty has not imposed on them2- there are some words have multiple readings such as ( such as rafat _ aasy _ track of them _ radwan )3- it concluded that the order has two sides to express them they read together rafat and mercy . the second face : to it mounted by a deleted4- these monastic against them and the rafat and mercy are the creation of God almighty.5- How to describe God almighty Jews and Christians illogical , arrogant and bullying supplication the prophet and the diligence and greed to take the money of people unlawfully6- rental in eating money and usury in verdicts7- clear up the almighty to eat the most money ,not eating8- clear up the almighty how have been involved with God another God in the analysis of the sacred and the prohibition of muslim.9- he mentioned his conditions of Jews and Christians , and they him aberration and misguidance .Finally , I ask God almighty to preserve Islam and Muslim and to make this country safe and protect him from the evil enemies . and support him on the enemies of the faith that the lord and yes sire protagonist and makes the best of our knowledge purely for GOD sake and peace and blessings be upon our master and his family and him